Synthesis and characterization of Segmented polyurethanes based on polyethylene and polytetramethylene glycols (part I: Synthesis and characterization) - Lan, Pham Ngoc; Schacht, E. (VNU Journal of Science: Natural Sciences and Technology; Vol 19 No 4, 2003)
Abstract